2015
DOI: 10.1103/physrevd.91.115024
|View full text |Cite
|
Sign up to set email alerts
|

Zmass limits and the naturalness of supersymmetry

Abstract: The discovery of a 125 GeV Higgs boson and rising lower bounds on the masses of superpartners have lead to concerns that supersymmetric models are now fine-tuned. Large stop masses, required for a 125 GeV Higgs, feed into the electroweak symmetry breaking conditions through renormalization group equations forcing one to fine-tune these parameters to obtain the correct electroweak vacuum expectation value. Nonetheless, this fine-tuning depends crucially on our assumptions about the supersymmetry breaking scale.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 153 publications
(182 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, we applied a running of the VEV. We found that in particular the last three changes moved our results with DR renormalization in the top/stop sector close to those of the other codes applying solely DR renormalization, FlexibleSUSY [75], NMSSMTools [62][63][64], SOFTSUSY [65,66,138] and SPHENO [73,74]. The results of these codes and NMSSMCALC (applying the DR scheme) have been compared in [81].…”
Section: Discussion Of the Renormalization Schemesmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, we applied a running of the VEV. We found that in particular the last three changes moved our results with DR renormalization in the top/stop sector close to those of the other codes applying solely DR renormalization, FlexibleSUSY [75], NMSSMTools [62][63][64], SOFTSUSY [65,66,138] and SPHENO [73,74]. The results of these codes and NMSSMCALC (applying the DR scheme) have been compared in [81].…”
Section: Discussion Of the Renormalization Schemesmentioning
confidence: 62%
“…The spectrum generation of different SUSY models, including the NMSSM, on the other hand, is possible through the interface of SARAH [49,[69][70][71][72] with SPheno [73,74]. In the same spirit, SARAH has been interfaced with the package FlexibleSUSY [75,76]. All these programs include the Higgs mass corrections up to two-loop order, where in particular the two-loop corrections are obtained in the effective potential approach.…”
Section: Introductionmentioning
confidence: 99%
“…Also the dominant two-loop corrections to λ SM of order O(α 2 t αs) have been included in this reference. These results were implemented into the code SusyHD [23] and also FlexibleSUSY [69,70] uses the matching conditions from literature.…”
Section: Split-susy: Mssm → Sm and Electroweakinos And Gluinosmentioning
confidence: 99%
“…Moreover, different hybrid methods that combine both approaches have been recently developed in order to take profit of the features of each one. FlexibleSUSY [46], based on SARAH [47], implements a hybrid method called Flexible-EFT-Higgs [48]. This approach was also included into the program SPheno [49,50].…”
Section: Introductionmentioning
confidence: 99%